2013
DOI: 10.1186/1752-1947-7-292
|View full text |Cite
|
Sign up to set email alerts
|

Lateral pharyngeal wall myeloid sarcoma as a relapse of acute biphenotypic leukemia: a case report and review of the literature

Abstract: IntroductionMyeloid sarcoma is a rare extramedullary malignant tumor composed of immature myeloid cells. The tumor can affect any part of the body. Involvement of the oral cavity and nasopharynx has been reported in 50 cases. We report a case describing myeloid sarcoma affecting the lateral pharyngeal wall.Case presentationA 31-year-old Arabian man who had acute biphenotypic leukemia treated with chemoradiation and allogeneic stem cell transplant was referred to our department with sore throat and a mass lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have demonstrated that immunophenotype is of utmost importance in determining the diagnosis of GS (3)(4)(5). In particular, the literature has focused on the CD13 and CD68 markers for granular monocytic and macrophagic cells, MPO and CD117 markers for myeloid differentiation, lysozyme marker for monocytic lineage, CD43 marker for myeloid cells as well as T cells and B precursors, and CD34 and terminal deoxynucleotidyl transferase (TdT) markers for immature cells (10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated that immunophenotype is of utmost importance in determining the diagnosis of GS (3)(4)(5). In particular, the literature has focused on the CD13 and CD68 markers for granular monocytic and macrophagic cells, MPO and CD117 markers for myeloid differentiation, lysozyme marker for monocytic lineage, CD43 marker for myeloid cells as well as T cells and B precursors, and CD34 and terminal deoxynucleotidyl transferase (TdT) markers for immature cells (10).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this association is still unknown, but may be attributed to a pattern of graft-versus-leukemia surveillance or to the biology of high-risk AML treated with transplantation (5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 5 ] Mixed phenotypic acute leukemia (MPAL) presenting as MS is exceedingly rare with only three cases described till date. [ 6 7 8 ] Our case of MS is unique not only in its unusual location of thyroid, but its also a rare underlying morphology of MPAL.…”
Section: Introductionmentioning
confidence: 99%